Efecto de fitorreguladores para la inducción de embriones somáticos en explante foliar de Myrciaria dubia (Kunth) McVaugh “camu camu” - Valles Najar, Barbara Susana (2025)
Myrciaria dubia, or "camu camu," accumulates high concentrations of vitamin C in its fruits, offering potential health benefits. However, the inconsistency in the concentrations of this vitamin makes its marketing and global valuation difficult. To address this problem, biotechnological tools such as somatic embryogenesis could allow the in vitro cultivation of elite plants that maintain the highest quality standards. The objective of this study was to determine the effect of phytoregulators for the induction of somatic embryos in leaf explants of M. dubia. Twenty-five treatments were established that combined different concentrations (0; 1.5; 6; 15 and 30 µM) of auxins and cytokinins. The auxins used were indoleacetic acid, 2,4-dichlorophenoxyacetic acid, and naphthaleneacetic acid; and the cytokinins were kinetin, 6-benzylaminopurine, and thidiazuron. The results indicated that the phytoregulators induced callogenic and embryogenic responses in the explants. Callus formation was predominantly observed in treatments that combined auxins with cytokinins, reaching up to 60% of explants with callus formation. Somatic embryos were observed in 64% of the explants from the T7 treatment (1.5 µM auxins + 1.5 µM cytokinins) reaching the globular stage. In conclusion, the combination of auxins and cytokinins induce embryogenic responses, but the success rate was low, so further experiments are needed.